Combined experimental/numerical investigation of directional moisture diffusion in glass/epoxy composites. (20th October 2017) - Rocha, I.B.C.M.; Raijmaekers, S.; van der Meer, F.P.; Nijssen, R.P.L.; Fischer, H.R.; Sluys, L.J.
Abstract: A combined experimental and numerical investigation is conducted on the anisotropic water diffusion behaviour of unidirectional glass/epoxy composites. Experimental diffusivity values are obtained by immersing thin material slices for each of its planes of orthotropy extracted from a thick composite panel and interphase measurements are performed using thermal analysis. In order to elucidate the observed anisotropy, the diffusion process is modelled at the microscale using a representative volume element (RVE) of the material with random fibre distribution. Water concentration gradients are applied to the micromodel and a homogenisation procedure is used to retrieve the macroscopic diffusivity coefficients. The influence of the interphase around the fibres on the diffusion process is modelled by making the matrix diffusivity a function of the distance to the nearest fibre using a level set field. The models are used to fit the experimental data and test a number of hypotheses that may explain the observed anisotropy. The effect of fibres acting as barriers for water movement is found to partially explain the observed transverse diffusivity. However, a fit is only obtained by allowing faster diffusivity at the interphase. In the longitudinal direction, a fit can only be found by allowing for orthotropic interphase diffusivity.